Open Classroom in Natural Spaces: an Experience in the Ramón Álvarez Forest - Ana Isabel Pereira-Pérez; Nuria Mairena-Rodríguez (Universidad Nacional, Costa Rica, 2011)
This paper shows the experience of bringing the natural spaces closer to the educational reality as a strategy to teach values in environmental education and conservation. This open classroom activity was developed by professors and students of the Chorotega regional center, of the Universidad de Costa Rica, in the Ramón Álvarez forest. Teachers and children from the different educational institutions of this region have participated in the project.